Lived Experience of Parents with Technology-Dependent Children: A Phenomenological Study - Sara Raquel Machado Lemos; Luísa Maria Costa Andrade; Lígia Maria Monteiro Lima; Isabel Maria Fernández-Medina; Maria Do Céu Aguiar Barbieri-Figueiredo (SAGE Publishing, 2024)
Caring for technology-dependent children significantly impacts the family unit, a topic that has not been researched in Portugal. Understanding this impact can help nurses to improve their interventions. This study aimed to describe the lived experiences of parents with technology-dependent children using a qualitative descriptive design. We applied Giorgi's approach to analyze 10 individual semi-structured interviews with parents recruited through a children's hospital in Portugal. Our analysis identified two major themes: (1) Discovering a new parenthood: parent and caregiver, comprising two subthemes: Family reorganization and Learning to use a medical device; (2) Reconciling daily life with the needs of the technology-dependent children, comprising two subthemes: Importance of support systems and Experiencing difficulties. These results indicate that parents experience a wide range of concerns and challenges in managing medical devices, starting from the moment the need for a device is communicated and continuing through the process of learning and providing care. This journey involves significant changes in family dynamics and is marked by sacrifice and adaptation, supported by family, formal support systems, and healthcare professionals. Our findings provide valuable insights into the vulnerabilities faced by these parents and highlight how nursing care can enhance the quality of care for these families.